2014
DOI: 10.1614/wt-d-13-00124.1
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer and Fluazifop-P Inputs for Winter Bentgrass- (Agrostis hyemalis) Infested Lowbush Blueberry Fields

Abstract: Winter bentgrass is a common, shallow-rooted perennial weed of lowbush blueberry fields. This unique production system is typically managed on a biannual cycle with blueberry shoot growth and floral bud development occurring in the first year (vegetative year) and berries harvested in the second year (crop year). An experiment was conducted in two commercial blueberry fields to determine the impact of 0, 143, or 286 kg ha−1of 14–18–10 fertilizer applied in the vegetative year, and fluazifop-P applications in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Glufosinate and foramsulfuron did not reduce blueberry stem density, stem height, or flower buds per stem, but the data also suggest that suppression of fescues does not increase yield potential of wild blueberry fields. Initial studies with hexazinone and other preemergence herbicides found large increases in blueberry stem density and flower buds per stem following weed control (Jensen 1986; Yarborough et al 1986), but lack of blueberry yield potential and yield response to weed control is not uncommon in small plot trials conducted since the widespread adoption of hexazinone and other herbicides (Boyd et al 2014; Boyd and White 2010; Kennedy et al 2010). Increases in parameters such as blueberry stem density and flower buds per stem can also take several years to become evident following initiation of weed control treatments (Eaton 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glufosinate and foramsulfuron did not reduce blueberry stem density, stem height, or flower buds per stem, but the data also suggest that suppression of fescues does not increase yield potential of wild blueberry fields. Initial studies with hexazinone and other preemergence herbicides found large increases in blueberry stem density and flower buds per stem following weed control (Jensen 1986; Yarborough et al 1986), but lack of blueberry yield potential and yield response to weed control is not uncommon in small plot trials conducted since the widespread adoption of hexazinone and other herbicides (Boyd et al 2014; Boyd and White 2010; Kennedy et al 2010). Increases in parameters such as blueberry stem density and flower buds per stem can also take several years to become evident following initiation of weed control treatments (Eaton 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Increases in parameters such as blueberry stem density and flower buds per stem can also take several years to become evident following initiation of weed control treatments (Eaton 1994). Growers report decreased yields and difficulty harvesting fields with heavy fescue infestations, and there is evidence that perennial grasses respond favorably to fertility inputs in wild blueberry (Boyd et al 2014). Fescues, as well as other perennial grasses, therefore need to be managed despite lack of an immediate increase in yield potential, and our results provide important data on efficacy and crop safety of glufosinate and foramsulfuron in wild blueberry.…”
Section: Resultsmentioning
confidence: 99%
“…Yield increases were common following the removal of grasses and other weeds with hexazinone or terbacil in initial field trials with these herbicides (Smagula and Ismail 1981;Jensen 1986;Yarborough et al 1986), although Jensen (1985) acknowledged variation in crop response to weed control across genets and sites in early trials. Other recent research has also failed to demonstrate consistent increases in yield potential or yield following control of various weed species in small-plot trials (Boyd and White 2010;Kennedy et al 2010;Boyd et al 2014;White and Kumar 2017). Yield increases can also require multiple years to manifest following weed control measures (Eaton 1994), further complicating these measurements in short-term research trials.…”
Section: Treatment Effects On Wild Blueberrymentioning
confidence: 99%
“…Seeds shatter easily from the panicle inflorescence (Munro et al 2014) and secondary dispersal of non-dormant seeds by harvesting equipment may be contributing to the increased prevalence of this weed in wild blueberry fields in Nova Scotia (Boyd and White 2009). Yield losses from hair fescue have not been consistently demonstrated in research trials to date (White and Kumar 2017), although red fescue (Festuca rubra L.) and other perennial grass species reduce the yield potential and (or) yield of wild blueberry (Boyd et al 2014;Sikoriya 2014). Growers also report yield reductions in fields where hair fescue has formed dense sods, and development of new management strategies for hair fescue and other perennial grasses is a high priority for the wild blueberry industry due to limited management options for these weeds (AAFC 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Growers are therefore lacking both basic biological data and practical efficacy data, to implement seedling management as a component of an overall fescue management plan. Control of grasses increases the yield potential of lowbush blueberry fields (Boyd et al ., ). It is therefore imperative that new knowledge of grass population biology be combined with new, cost‐effective management options to ensure the ongoing ability of growers to manage these yield‐limiting weeds.…”
Section: Introductionmentioning
confidence: 97%